Unveiling the Mycobacterial Spectrum in Endophthalmitis: A Systematic Review of Etiological Agents - Yunialthy Dwia Pertiwi; Andi Irhamnia Sakinah; Lisa Tenriesa Muslich; Andi Rofian Sultan; Muhammad Nasrum Massi; Mochammad Hatta; Firdaus Hamid (International Journal of Mycobacteriology)
Endophthalmitis is a severe intraocular infection that poses a substantial risk of permanent vision loss if not promptly diagnosed and treated. Among its diverse etiologies, infections caused by Mycobacterium species are notably rare yet clinically significant due to their slow-growing nature and atypical presentations, which complicate diagnosis and management. This systematic review examines the role of Mycobacterium species in cases of endophthalmitis, with a particular focus on their etiologies and diagnostic challenges. A comprehensive search of electronic databases yielded 14 studies published between 2014 and 2024, providing insights into the identification and characterization of these pathogens in intraocular infections. The findings highlight the importance of heightened clinical suspicion and the use of advanced microbiological techniques to detect Mycobacterium species, given their subtle clinical manifestations and prolonged culture requirements. Addressing these challenges is critical for timely intervention and optimizing patient outcomes. This review underscores the need for further research to establish standardized diagnostic protocols and effective treatment strategies for Mycobacterium-associated endophthalmitis. Such efforts will enhance understanding of these rare but impactful infections, ultimately contributing to improved clinical management and preservation of vision.